Seizures in dominantly inherited Alzheimer disease. (30th August 2016) - Zarea, Aline; Charbonnier, Camille; Rovelet-Lecrux, Anne; Nicolas, Gaël; Rousseau, Stéphane; Borden, Alaina; Pariente, Jeremie; Le Ber, Isabelle; Pasquier, Florence; Formaglio, Maite; Martinaud, Olivier; Rollin-Sillaire, Adeline; et al.
Abstract : Objective: To assess seizure frequency in a large French cohort of autosomal dominant early-onset Alzheimer disease (ADEOAD) and to determine possible correlations with causative mutations. Methods: A national multicentric study was performed in patients with ADEOAD harboring a pathogenic mutation within PSEN1, PSEN2, APP, or a duplication of APP, and a minimal follow-up of 5 years. Clinical, EEG, and imaging data were systematically recorded. Results: We included 132 patients from 77 families: 94 PSEN1 mutation carriers (MCs), 16 APP duplication carriers, 15 APP MCs, and 7 PSEN2 MCs. Seizure frequency was 47.7% after a mean follow-up of 8.4 years (range 5–25). After 5-year follow-up and using a Cox model analysis, the percentages of patients with seizures were respectively 19.1% (10.8%–26.7%) for PSEN1, 28.6% (0%–55.3%) for PSEN2, 31.2% (4.3%–50.6%) for APP duplications, and no patient for APP mutation. APP duplication carriers showed a significantly increased seizure risk compared to both APP MCs (hazard ratio [HR] = 5.55 [95% confidence interval 1.87–16.44]) and PSEN1 MCs (HR = 4.46 [2.11–9.44]). Among all PSEN1 mutations, those within the domains of protein hydrophilic I, transmembrane II (TM-II), TM-III, TM-IV, and TM-VII were associated with a significant increase in seizure frequency compared to other domains (HR = 4.53 [1.93–10.65], p = 0.0005). Conclusions: Seizures are a common feature of ADEOAD. In this population, risk was significantly higher in the APP duplication group than in all other groups. Within PSEN1, 5 specific domains were associated with a higher seizure risk indicating specific correlations between causative mutation and seizures.